Migracje zagraniczne w krajach Unii Europejskiej w warunkach kryzysu gospodarczego - Nowotnik, Dariusz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
Migration, or the movement of population, aimed at temporary or permanent change of residence (PWN) and has always accompanied the mankind. There are various reasons for migration, mainly economic and political. Sometimes the population moves to experience other cultures and countries (tourism - migration). The intensity of migration movement and its direction reflects the economic status, stage of development, and social conditions in these areas. Countries which are attractive to tourists and have a good tourist base are characterized by a well-developed economy and low unemployment, as well as an attractive geographical location which makes them the most desirable places for migration. On the other hand, countries which are still passing the structural changes in the national economy, having a non-oriented domestic and foreign policy, faced with demographic problems and unemployment, located in very attractive geographic areas, are the countries attracting the immigrants. Such dependence can be seen between the countries of Western and Central Europe and Eastern European countries. The change of some factors, or destabilization of the overall situation in the world (as it happened in 2007 as a result of the global economic crisis) causes the profound changes in migration flows and hence the need to change the approach to immigration by individual countries. However, migration (depending on its type) can cause gains or losses for the immigration and emigration countries as the changing global economic situation is becoming increasingly important.